Experimental Investigation of Axial Pull-out Behavior of Glued-in Threaded Rods in Cross-Laminated Timber - Zhibin Ling; Zheng Li; Zhoujun Li; Chao Yang; Wei Zheng; Lingfeng Zhang (BioResources)
Cross-laminated timber (CLT), known for its high performance, prefabrication, low carbon emission, and eco-friendliness, has gained widespread adoption in the construction industry. Glued-in rod (GiR) connections, which offer a concealed appearance, high strength, withdrawal stiffness, ease of construction, and fire resistance, have become a promising solution for CLT structures. This study experimentally investigated the axial pull-out behavior of GiR connections in CLT. Forty-five CLT specimens with single GiR were designed and tested under pull-out conditions. The experimental variables included embedment length, threaded rod diameter, and rod-to-grain angle (parallel and perpendicular). The results revealed that CLT connections with GiR parallel to the grain exhibited an ascending load-slip response until peak load, followed by a sudden failure, while those with GiR perpendicular to the grain showed a linear increase to peak load with a subsequent gradual load reduction. Increasing the embedment length from 5 d to 15 d enhanced the pull-out load but decreased the average bond stress. Additionally, larger rod diameters led to higher pull-out loads and withdrawal stiffness within a certain range but reduced the average bond stress. The study also evaluated the effectiveness of existing bond stress-slip models and pull-out load prediction models for GiR connections in CLT, providing a foundation for future standardization efforts.